[Rezension von: Herbst, Thomas, 1953-, A valency dictionary of English] - Nesselhauf, Nadja (English language and linguistics, 2005)
Thomas Herbst, David Heath, Ian F. Roe, and Dieter Götz, A valency dictionary of English: a corpus-based analysis of the complementation patterns of English verbs, nouns and adjectives. Berlin and New York: Mouton de Gruyter, 2004. Pp. xlii + 962. ISBN 3 11 017194 5 - Volume 9 Issue 2